PEMBERDAYAAN MASYARAKAT EKONOMI MELALUI PENINGKATAN LITERASI KEUANGAN DAN E-COMMERCE PADA UMKM KELURAHAN WONODRI SEMARANG - Riyanto Riyanto; Novika Wahyuhastuti; Aryan Eka Prastya Nugraha; Inayah Adi Sari (Jurnal Abdimas Bina Bangsa, 2022)
The purpose of this Community Partnership Program is to provide solutions to the problems faced by partners, namely business management problems and product marketing of SMEs in Wonodri Village and to develop a culinary business into a business with quality products and competitiveness in the market with effective business finance management. This PKM activity was carried out in Wonodri Village, South Semarang District, Semarang City. Solutions Offered To The Process Of Marketing Products Through E-Commerce. This activity is an effort to increase partner's income. Solutions related to finance are provided with household and SME finance training with the output in the form of a financial module while it is related to SME marketing through Whatsapp business and marketplace media. In the aspect of management, the implementation method is provided by providing training in the preparation of bookkeeping in managing business finances. In this stage, partners will receive training and assistance from experts in preparing working capital, to carrying out bookkeeping related to income and costs. From the problems faced by partners and solutions provided with implementation methods adapted to the conditions of partners